PENGARUH PERAN ORANG TUA TERHADAP TINGKAT DEPRESI PADA REMAJA PUTRI DI DESA MARGA MULYA - Siti Najwalillah (Yayasan Nusantara Hasana Berdikari, 2023)
Adolescence is characterized by great changes including the need to adapt to physical and psychological changes, the search for identity and the formation of new relationships including appreciating sexual feelings. Depression usually occurs when the stress experienced by a person does not subside and the depression experienced correlates with a dramatic event that has just occurred or happened to a person. Objective of the study is to determine the factors that affect the level of depression in young women in Marga Mulya Village. This research is quantitative, by taking a data method on the role of parents with depression levels in young women in Marga Mulya Village using Google Form, obtained by distributing questionnaires to 120 respondents using web-based interactive services. Chi-square test, obtained a p-value of 0.361 > 0.005 which means that there is no influence of parental roles with depression levels in young women in Marga Mulya Village. There is no influence on the role of parents with the level of depression experienced by young women in Marga Mulya Village.